Pendekatan Solutif Dakwah Islam Untuk Kenakalan Remaja - Penmardianto, Penmardianto (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2022)
Over time and the increasing number of the younger generation (adolescents), the rate of juvenile delinquency that occurs is increasing. This article discusses about juvenile delinquency, starting from its understanding, theory, causes and consequences, Islamic views on how to deal with it and solutions for Islamic da'wah in overcoming it. Juvenile delinquency that is developing today is a social phenomenon that must be found a way out. If juvenile delinquency is allowed to develop, it will bring great danger to the life of society, nation and state. Juvenile delinquency must be anticipated considering the many consequences it can cause, ranging from endangering the teenager concerned, to causing anxiety and fear from the parents of the teenager concerned, and even chaos in the environment where the teenager is domiciled. In overcoming the problem of juvenile delinquency, it cannot only rely on one-sidedness, because the causes that motivate the emergence of these juvenile acquaintances are so complex, therefore, in overcoming juvenile delinquency, it is necessary to synchronize the parents concerned with the education at school as well as adequate control in life in the school. community environment.